2001
DOI: 10.1143/jjap.40.5543
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Hydrothermally Deposited Lead Zirconate Titanate (PZT) Thin-Film

Abstract: The modifications in plasma parameters and heating power under conditions of pulsed poloidal current drive (PPCD) in Reversed Field eXperiment (RFX) are modelled by the one-dimensional transport code RITM (Radiation from Impurities in Transport Model). Several channels for the PPCD effects on plasma confinement are taken into account: dissipation of externally driven poloidal currents, reduction in the electric field induced by the dynamo and decrease in magnetic fluctuations. It is demonstrated that the exter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…These material salts were agitated in KOH aqueous solution as reactive solutions. Although the value is too small compared with that of bulk, the value is almost same that of a hydrothermal PZT film in previous other group work [13]. After the foils and the reactive solution are set in a sealed autoclave, the hydrothermal process was carried out at 140 ºC for 24 hours.…”
Section: Methodssupporting
confidence: 65%
“…These material salts were agitated in KOH aqueous solution as reactive solutions. Although the value is too small compared with that of bulk, the value is almost same that of a hydrothermal PZT film in previous other group work [13]. After the foils and the reactive solution are set in a sealed autoclave, the hydrothermal process was carried out at 140 ºC for 24 hours.…”
Section: Methodssupporting
confidence: 65%
“…9) We have already reported that, by using the hydrothermal deposition process for PZT, we can fabricate vibrators that have higher limitation of vibration velocity and higher linearity of the frequency response under high-intensity operation. 10,11) It is important to know how the limitation of the vibration velocity is. The static factors such as piezoelectric constants, d 31 , d 33 , and e 31 , were measured to evaluate the performance of the material in most of the cases for the evaluation of piezoelectric vibrators.…”
Section: Introductionmentioning
confidence: 99%
“…where T C = 425°C is the Curie temperature and T RT = 25°C is the room temperature; ␣ para PZT , ␣ ferro PZT , and ␣ Ti are CTEs for paraelectric PZT, ferroelectric PZT, and Ti, respectively. In addition, E = 1.3ϫ 10 10 N / m 2 is Young's modulus for hydrothermal PZT film 15 and v denotes Poisson's ratio and is reasonably assumed to be 0.2. At Curie temperature, ͑T͒ has its maximal value of 145.6 MPa, which is much more than the residual stress in PZT films without any cracks that is about 117.21 MPa.…”
mentioning
confidence: 99%